Neuroprotective potential of phytochemicals - Kumar, G. Phani; Khanum, Farhath (Pharmacognosy Reviews, 2012)
Cognitive dysfunction is a major health problem in the 21st century, and many neuropsychiatric disorders and neurodegenerative disorders, such as schizophrenia, depression, Alzheimer’s Disease dementia, cerebrovascular impairment, seizure disorders, head injury and Parkinsonism, can be severly functionally debilitating in nature. In course of time, a number of neurotransmitters and signaling molecules have been identifi ed which have been considered as therapeutic targets. Conventional as well newer molecules have been tried against these targets. Phytochemicals from medicinal plants play a vital role in maintaining the brain's chemical balance by infl uencing the function of receptors for the major inhibitory neurotransmitters. In traditional practice of medicine, several plants have been reported to treat cognitive disorders. In this review paper, we attempt to throw some light on the use of medicinal herbs to treat cognitive disorders. In this review, we briefl y deal with some medicinal herbs focusing on their neuroprotective active phytochemical substances like fatty acids, phenols, alkaloids, fl avonoids, saponins, terpenes etc. The resistance of neurons to various stressors by activating specifi c signal transduction pathways and transcription factors are also discussed. It was observed in the review that a number of herbal medicines used in Ayurvedic practices as well Chinese medicines contain multiple compounds and phytochemicals that may have a neuroprotective effect which may prove benefi cial in different neuropsychiatric and neurodegenerative disorders. Though the presence of receptors or transporters for polyphenols or other phytochemicals of the herbal preparations, in brain tissues remains to be ascertained, compounds with multiple targets appear as a potential and promising class of therapeutics for the treatment of diseases with a multifactorial etiology.
Keywords: Antioxidants; medicinal plants; neuroprotective herbs; nootropics; phytochemicals